A prospective, active haemovigilance study with combined cohort analysis of 19 175 transfusions of platelet components prepared with amotosalen–UVA photochemical treatment. Issue 4 (15th May 2015) - Knutson, F.; Osselaer, J.; Pierelli, L.; Lozano, M.; Cid, J.; Tardivel, R.; Garraud, O.; Hervig, T.; Domanovic, D.; Cukjati, M.; Gudmundson, S.; Hjalmarsdottir, I. B.; et al.
<x xml:space="preserve">Abstract</x> Background and Objectives A photochemical treatment process (PCT) utilizing amotosalen and UVA light (INTERCEPT™ Blood System) has been developed for inactivation of viruses, bacteria, parasites and leucocytes that can contaminate blood components intended for transfusion. The objective of this study was to further characterize the safety profile of INTERCEPT‐treated platelet components (PCT‐PLT) administered across a broad patient population. Materials and Methods This open‐label, observational haemovigilance programme of PCT‐PLT transfusions was conducted in 21 centres in 11 countries. All transfusions were monitored for adverse events within 24 h post‐transfusion and for serious adverse events (SAEs) up to 7 days post‐transfusion. All adverse events were assessed for severity (Grade 0–4), and causal relationship to PCT‐PLT transfusion. Results Over the course of 7 years in the study centres, 4067 patients received 19 175 PCT‐PLT transfusions. Adverse events were infrequent, and most were of Grade 1 severity. On a per‐transfusion basis, 123 (0·6%) were classified an acute transfusion reaction (ATR) defined as an adverse event related to the transfusion. Among these ATRs, the most common were chills (77, 0·4%) and urticaria (41, 0·2%). Fourteen SAEs were reported, of which 2 were attributed to platelet transfusion (<0·1%). No case of transfusion‐related acute lung injury, transfusion‐associated graft‐versus‐host disease, transfusion‐transmitted infection or death was attributed to the transfusion of PCT‐PLT. Conclusion This longitudinal haemovigilance safety programme to monitor PCT‐PLT transfusions demonstrated a low rate of ATRs, and a safety profile consistent with that previously reported for conventional platelet components.